Factors associated with regional bias of pfcrt (plasmodium falciparum chloroquine resistance transporter) haplotypes in Nepal. - Banjara, MR; Imwong, M; Petmitr, S; Sirawaraporn, W; Joshi, AB; Chavalitshewinkoon-Petmitr, P (2011)
Evidences of reappearance of chloroquine sensitive Plasmodium falciparum haplotypes after cessation of chloroquine in many countries provide a rationale for the search of chloroquine sensitive haplotypes in P. falciparum isolates in Nepal where the use of chloroquine for falciparum malaria treatment has been ceased since 1988. P. falciparum chloroquine resistant transporter gene (pfcrt) haplotypes were determined and the factors associated with pfcrt haplotypes in the Eastern and Central regions of Nepal were identified. Blood samples from 106 microscopy-positive falciparum malaria patients (62 from the Eastern and 44 from the Central region) were collected on filter paper. Pfcrt region covering codons 72-76 was amplified by PCR and sequenced. SVMNT haplotype was predominant in the Central region, whereas CVIET haplotype significantly more common in the Eastern region. In multivariable analysis of factors associated with CVIET haplotype, the Eastern region and parasite isolates from patients visiting India within one month are significant at 5% level of significance. These findings suggest that antimalarial pressure is different between Eastern and Central regions of Nepal and there is a need of an effective malaria control program in the border areas between India and Nepal.